Studies on climatic and environmental changes during the last few hundred years using ice cores from various sites in Nordaustlandet, Svalbard (scientific paper) - Watanabe, Okitsugu; Motoyama, Hideaki; Igarashi, Makoto; Kamiyama, Kokichi; Matoba, Sumito; Goto-Azuma, Kumiko; Narita, Hideki; Kameda, Takao
Ice coring and snow cover observations have been carried out at 3 sites in Nordaustlandet, Svalbard since 1995. The results of stratigraphic analyses, and chemical and δ^<18>O analyses from Vestfonna and Austfonna cores are presented here. The results from these sites show that most of the chemical constituents contained in the initial snow cover still remained in the ice cores, although re-distribution of them by melt water percolation had occurred. Anthropogenic increases in trace metals, sulfate and nitrate since about 1950 are detected. This suggests that ice-core chemistry records from Nordaustlandet, Svalbard, can be useful to reconstruct past atmospheric conditions. In addition to chemical records, δ^<18>O records, that correlate well with the temperature records in Svalbard, can be used to reconstruct past temperature changes. application/pdf journal article